Health-Related Quality of Life following Reconstruction for Common Head and Neck Surgical Defects. Issue 6 (December 2016) - Cohen, Wess A.; Albornoz, Claudia R.; Cordeiro, Peter G.; Cracchiolo, Jennifer; Encarnacion, Elizabeth; Lee, Meghan; Cavalli, Michele; Patel, Snehal; Pusic, Andrea L.; Matros, Evan
Abstract : Background: Improved understanding and management of health-related quality of life represents one of the greatest unmet needs for patients with head and neck malignancies. The purpose of this study was to prospectively measure health-related quality of life associated with different anatomical (head and neck) surgical resections. Methods: A prospective analysis of health-related quality of life was performed in patients undergoing surgical resection with flap reconstruction for stage II or III head and neck malignancies. Patients completed the European Organization for Research and Treatment of Cancer Core Quality-of-Life Questionnaire-30 and the European Organization for Research and Treatment of Cancer Head and Neck Cancer Module-35 preoperatively, and at set postoperative time points. Scores were compared with a paired t test. Results: Seventy-five patients were analyzed. The proportion of the cohort not alive at 2 years was 53 percent. Physical, role, and social functioning scores at 3 months were significantly lower than preoperative values ( p < 0.05). At 12 months postoperatively, none of the function or global quality-of-life scores differed from preoperative levels, whereas five of the symptom scales remained below baseline. At 1 year postoperatively, maxillectomy, partial glossectomy, and oral lining defects had better function and fewer symptoms than mandibulectomy, laryngectomy, and total glossectomy. From 6 to 12 months postoperatively, partial glossectomy and oral lining defects had greater global quality of life than laryngectomies ( p < 0.05). Conclusions: Postoperative health-related quality of life is associated with the anatomical location of the head and neck surgical resection. Preoperative teaching should be targeted for common ablative defects, with postoperative expectations adjusted appropriately. Because surgery negatively impacts health-related quality of life in the immediate postoperative period, the limited survivorship should be reviewed with patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.